Vernacular solutions for managing energy use in mountain areas with cold and dry climate: case study of Azerbaijan – Iran - Ebrahimi, Ahad Nejad; Rahimian, Farzad Pour; Loron, Mehrdad Sahraei (Universiti Putra Malaysia, 2012)
Understanding vernacular way of energy-saving and providing low-impact thermal comfort in the building of every region may have significant impacts on developing well-established green strategies for the new architecture for that region. The conducted preliminary desktop research revealed fundamental similarities among architectural approaches of different regions of Iran. The conducted literature review also revealed that much research has been done for exploring different angles of vernacular sustainable methods of architecture in central arid zone of Iran which is often recognised as the representative of the traditional architecture of Iran; as this part already contributes to almost three fourth of the total area of Iran. In other words, the creative methods of adopting sustainable architecture in other parts have been neglected by far. This fact also applies to the well-established vernacular architecture of Azerbaijan the history of which backs to more than 10,000 years ago. This research investigated the innovative methods through which the architects of cold and dry Azerbaijan managed energy use in the vernacular buildings. The study adapted field studies as well as archival research followed by qualitative methods of content analysis. The research discovered the similarities and differences between the vernacular methods of energy saving in this part of Iran and those for the arid central parts of the country. The results revealed that although there are a lot of similarities between these two architectural styles, the traditional architects of Azerbaijan have had various innovative and sustainable methods in construction and structure of the buildings which are exclusive for this region only. This research contributes with highlighting particular and significant approaches of the ancient sustainable architecture of Azerbaijan which could be used as a reference for further development and adaptation in designing new buildings in this part of the world.